POLIGAMI DAN KETIDAKADILAN GENDER DALAM UNDANG-UNDANG PERKAWINAN DI INDONESIA - Nur Kholis; Jumaiyah Jumaiyah; Wahidullah Wahidullah (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2017)
The article 4 clause 2 in the Act Number 1 Year 1974, mentioned that discrimination against women (wife) potentially in increasing the divorce rates. It can be minimized by creating a gender-based mindset, that will be the object of this research. This research will use qualitative methods with normative juridical approach. This research found that: firstly, that the Act Number 1 Year 1974 and its derivative laws such as Compilation of Islamic Law (KHI), has not reach yet the Pancasila values and also justice and humanity as the main mission of law. Secondly, the political configuration in the drafting of laws and “black and white” in understanding of religious texts are contribute to creating injustice. Thirdly, the justice is one of the goals of the law, so discrimination must be eliminated. This research provides a recommendation that polygamy in article 4 clause 2 in the Act Number 1 Year 1974 must be removed, and become the principle of monogamy absolutely.[]Diskriminasi terhadap perempuan (Isteri), sebagaimana tertuang pada Pasal 4 ayat 2 UU No. 1 Tahun 1974, berpotensi menciptakan tingginya angka perceraian. Meminimalisasi hal tersebut dengan membangun pemikiran berbasis keadilan gender merupakan tujuan dalam penelitian ini. Adapun metode yang dipilih adalah kualitatif dengan pendekatan yuridis-normatif. Hasil penelitian yang ditemukan; Pertama, bahwa UU No. 1 Tahun 1974 beserta perundang-undangan turunannya seperti KHI, masih jauh dari nilai-nilai Pancasila dan misi utama hukum; yaitu nilai keadilan dan kemanusiaan. Kedua, konfigurasi politik dalam produksi UU Perkawinan dan pemahaman teks agama yang “hitam-putih” adalah kontributor terciptanya ketidakadilan. Ketiga, salah satu tujuan hukum adalah keadilan, maka bentuk-bentuk diskriminasi harus dihapuskan. Artikel ini merekomendasikan penghapusan poligami dalam pasal 4 ayat 2 UU No.1 Tahun 1974, dan menjadikan monogami bersifat mutlak.